Diferenciais de desempenho acadêmico no ensino superior: evidências para os estudantes ingressantes por ações afirmativas na Universidade Federal de Goiás - Andrade, Kênia Rodrigues (2024)
The affirmative actions to reserve quotas promote access for socially vulnerable students, susceptible to discriminatory processes in Higher Education Institutions and contribute to the personal and social emancipation of the individual. Furthermore, for the formation of human capital, education plays a fundamental role in individual and collective protection against poverty and misery that plague society. It was observed that, in the specialized literature, there are divergent conceptions about the Quota System, especially about the academic performance of quota students. The main objective of this research was to analyze the academic performance of quota students, in relation to non-quota students, at the Federal University of Goiás (UFG), from 2016 to 2022. The research was carried out based on academic information from students in the degree and were collected on the Analisa/UFG Platform. Using STATA software, descriptive statistics and econometric techniques were estimated for treatment purposes, specifically the propensity score matching model. The results indicated significant differences between quota students and non-quota students, regarding the performance presented in the National High School Exam (ENEM) and the overall average performance presented during the undergraduate course. Other evidence showed that the differences in academic performance presented by students were heterogeneous in terms of academic degree (bachelor's degree and degree), the campus attended, the shift enrolled and the year of entry. It was also found that differences in performance were significantly reduced as students progressed through their undergraduate courses. This research seeks to contribute to the intense discussion that takes place in academia about students' academic performance of students, as well as to establish parameters for managers of the Institution analyzed and researchers who are interested in the topic.